2007
DOI: 10.2989/ajas.2007.32.2.10.207
|View full text |Cite
|
Sign up to set email alerts
|

The zooplankton community of Lake Abo Zaabal, a newly-formed mining lake in Cairo, Egypt

Abstract: Abo Zaabal Lake, a new mining lake at the outskirts of Cairo, receives domestic sewage from a nearby village. We examined its chemical and biological properties in order to develop a plan to improve its ecosystem services. The pH ranged between 7.8 and 8.5, salinity was 17ppt and conductivity was 28 mS cm -1 , indicating brackish water. The pelagic zooplankton community comprised Rotifera (16%), Protozoa (Ciliophora and Rhizopoda) (18%) and Copepoda (16%). Cladocera were seldom recorded. Hexarthra, Brachionus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…2) were due to the domestic wastewater discharge. This is in agreement with the findings of El-Bassat & Tyalor [28] , they reported that, nitrogen and phosphorus compounds are always present in domestic wastewaters. Nitrite is one of the dissolved inorganic nitrogen forms present in water bodies and can be used as pollution indicator.…”
Section: Resultssupporting
confidence: 93%
“…2) were due to the domestic wastewater discharge. This is in agreement with the findings of El-Bassat & Tyalor [28] , they reported that, nitrogen and phosphorus compounds are always present in domestic wastewaters. Nitrite is one of the dissolved inorganic nitrogen forms present in water bodies and can be used as pollution indicator.…”
Section: Resultssupporting
confidence: 93%
“…Among the species identified in the lake, B. angularis, F. longiseta, Keratella quadrata [19,57], B. longirostris and G. testudinaria ( [58][59][60] species grow in eutrophic conditions. According to QB/T Rotifera index, with the values of Karamık Lake with QB/T = 2.3 [46], Xochimilco Lake (Mexico) QB/T = 10 [81], Dojran Lake (Macedonia) QB/T = 1.6 [82], Beyşehir Lake (Beyşehir, Turkey) QB/T = 1.5-2 [30,31], Gölcük Lake (Ödemiş, İzmir, Turkey) QB/T = 5 [48], Ladik Lake (Samsun, Turkey) QB/T = 5 [10], Abo Zaabal Lake (Cairo, Egypt) QB/T = 4 [83], Liman Lake (Kızılırmak delta, Turkey) QB/T = 2.5 [84] were shown as eutrophic. Rotifera species were used as indicator while identifying the trophic condition of the lake.…”
Section: Copepodamentioning
confidence: 99%
“…Therefore, they are of considerable potential value' as water quality indicators (Sla´decek, 1983;Murugan et al, 1998). Zooplankton offer several advantages as indicators of environmental quality in both lakes and rivers: as a group, they have worldwide distribution and the species composition and community structure are sensitive for changes in environmental conditions, nutrient enrichment (Jha and Barat, 2003) and different levels of pollution (El-Bassat, 2007).…”
Section: Introductionmentioning
confidence: 99%